C-reactive Protein for Stroke Detection in the Emergency Department in Patients With Dizziness Without Neurological Deficits - Hong, Seok-In; Kim, June-Sung; Bae, Hong Jun; Kim, Won Young (Frontiers in Neurology, 2021)
Background: Stroke diagnosis can be challenging in patients with dizziness without neurologic deficits. The aim of this study was to evaluate the predictive value of C-reactive protein (CRP) for identifying acute stroke in such patients. Methods: Data from adult patients (>18 years) admitted to the emergency department from August 2019 to February 2020 were evaluated. The study subjects were 1,188 patients presenting with dizziness without neurological deficits whose serum CRP level was measured within 2 hours of arriving at the emergency department and who underwent brain magnetic resonance imaging. The relationship between CRP and acute stroke was analyzed using univariable and multivariable models. Results: Acute stroke was detected in 53 (4.4%) patients (40 with brain infarction, 10 with vertebrobasilar insufficiency, 2 with intracerebral hemorrhage, and 1 with subarachnoid hemorrhage). The CRP levels did not differ significantly between the acute stroke and non-stroke groups [0.10 (0.10–0.31) vs. 0.10 (0.10–0.16), P=0.074]. The area under receiver operating characteristic curve of CRP for acute stroke was not statistically significant (0.567, P=0.101). On multivariable analysis, the following variables were associated with acute stroke: age (odds ratio [OR], 1.041; 95% confidence interval [CI], 1.011–1.071), history of cerebrovascular accidents (OR, 1.823; 95% CI, 1.068–3.110), white blood cell count (OR, 1.126; 95% CI, 1.017–1.248), and hemoglobin (OR, 1.316; 95% CI, 1.056–1.640). However, CRP (P=0.183) was not associated with acute stroke. Conclusion: Serum CRP levels do not have significant discriminative value for identifying acute stroke in patients with dizziness without definite neurologic deficits.